INTERNAL ORGANIZATIONAL COMMUNICATION AND ISLAMIC VALUES-BASED CONFLICT RESOLUTION IN PESANTREN ORGANIZATIONS: A CASE STUDY OF PESANTREN AR-RAUDLATUL HASANAH - Muhammad May Fazri; Mario Nicholas Butar-Butar; Muhammad Randi Zulfikar; Yulia Jamaluddin Hasibuan; Feni Khairifa (Academic Solution Publisher, 2026)
This study examines the dynamics of internal organizational communication and conflict management at Pesantren Ar-Raudlatul Hasanah in Medan. Using a qualitative approach, the research explores how communication patterns among teaching staff function in maintaining coordination and resolving workplace conflicts. Data were collected through in-depth interviews with three informants representing different organizational levels: the Vice Director, a senior teacher, and a newly appointed teacher. The findings reveal that internal communication in the pesantren is characterized by structured vertical communication reinforced by intensive horizontal interactions among teachers. Conflicts that arise are generally triggered by differences in perception, miscommunication, and coordination issues rather than deep personal disputes. The study also demonstrates that Islamic values such as musyawarah, tabayyun, ukhuwah, tasamuh, and amanah play a significant role as normative frameworks guiding communication and conflict resolution. These values shape a distinctive conflict management model that combines dialogue, mediation, and leadership authority to maintain organizational harmony and institutional stability.